2005
DOI: 10.1007/s11267-005-3014-z
|View full text |Cite
|
Sign up to set email alerts
|

The release of nitrous oxide from the intertidal zones of two European estuaries in response to increased ammonium and nitrate loading

Abstract: Nitrous oxide (N 2 O) release and denitrification rates were investigated from the intertidal saltmarsh and mudflats of two European river estuaries, the Couesnon in Normandy, France and the Torridge in Devon, UK. Sediment cores and water were collected from each study site and incubated for 72 h in tidal simulation chambers. Gas samples were collected at 6 and 12 h intervals from the chambers during incubation. From these N 2 O emission rates were calculated. The greatest rates for both N 2 O production and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Our study on N 2 O flux at Bhitarkanika mangrove showed highest emission during postmonsoon, which is predominantly due to the availability of highly nitrogenous compound (Corredor et al . 1999; Kenny et al . 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our study on N 2 O flux at Bhitarkanika mangrove showed highest emission during postmonsoon, which is predominantly due to the availability of highly nitrogenous compound (Corredor et al . 1999; Kenny et al . 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observe estuarine bacterial activity directly, through incubation experiments (Kenny et al., ; Alongi et al., ; Chen et al., ), but most focus on the production of N 2 O, rather than consumption, so it is difficult to quantify the relative amount of these processes. However, significant negative N 2 O fluxes are recorded (e.g., Kreuzwieser et al., ; LaMontagne et al., ; Rajkumar et al., ; Adams et al., ).…”
Section: Controlling Factorsmentioning
confidence: 99%
“…Teixeira et al [21] found that N 2 O emissions at the sediment-water interface increased with seawater salinity. Kenny et al [22] found a strong positive correlation between N 2 O emission rates and ammonium concentration in a study concerning sediment nitrate concentrations in water, while Beaulieu et al [23] found no relationship between N 2 O yield and aquatic N-NO 3 in American streams.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly different nitrification and denitrification rates and N 2 O emissions have been reported at the sediment-water interface in different aquatic ecosystems due to high ecosystem complexity and differences between given locations: such differences can occur even between two bodies of water in the same location [24,25]. In this study, from August 2014 to July 2015, we examined nitrification and denitrification rates and N 2 O fluxes at the sediment-water interface in Taihu Lake, a large and important lake in China where few studies [20][21][22] have focused on these processes, allowing us to determine the dominant N 2 O emission process.…”
Section: Introductionmentioning
confidence: 99%